1998
DOI: 10.1038/3260
|View full text |Cite
|
Sign up to set email alerts
|

Loss of imprinting in normal tissue of colorectal cancer patients with microsatellite instability

Abstract: Loss of imprinting (LOI) is an epigenetic alteration of some cancers involving loss of parental origin-specific expression of imprinted genes. We observed LOI of the insulin-like growth factor-II gene in twelve of twenty-seven informative colorectal cancer patients (44%), as well as in the matched normal colonic mucosa of the patients with LOI in their cancers, and in peripheral blood samples of four patients. Ten of eleven cancers (91%) with microsatellite instability showed LOI, compared with only two of six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
192
2
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(208 citation statements)
references
References 32 publications
10
192
2
4
Order By: Relevance
“…The same phenomenon of relaxed IGF2 imprinting commonly occurs in Beckwith-Wiedemann syndrome (Weksberg et al, 1993;Reik et al, 1994), in children with the constitutional IGF2 overgrowth syndrome (Morison et al, 1996), and in the normal tissue adjacent to some cancers with relaxed imprinting (Okamoto et al, 1997;Cui et al, 1998).…”
Section: Introductionmentioning
confidence: 74%
“…The same phenomenon of relaxed IGF2 imprinting commonly occurs in Beckwith-Wiedemann syndrome (Weksberg et al, 1993;Reik et al, 1994), in children with the constitutional IGF2 overgrowth syndrome (Morison et al, 1996), and in the normal tissue adjacent to some cancers with relaxed imprinting (Okamoto et al, 1997;Cui et al, 1998).…”
Section: Introductionmentioning
confidence: 74%
“…Loss of imprinting at the 11p15.5 locus is a frequent event leading to the overexpression of genes in colorectal cancer (Cui et al, 1998). Therefore, loss of imprinting of ascl2 was hypothesized to contribute to the upregulation of ascl2 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, ascl2 has not been implicated in neoplastic transformation or progression, but there is circumstantial evidence to support a role for ascl2 in cancer. ascl2 resides at chromosome 11p15.5 and loss of imprinting at this locus is a frequent event in colorectal tumourigenesis (Cui et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of epigenetic changes in cancer development was shown in experiments in which reducing the level of DNA methylation to 10% of normal levels by introducing a hypomorphic allele of the DNA methyltransferase gene Dnmt1 was sufficient to induce cancer development in mice , presumably due to induction of chromosome instability . Studies on human colorectal cancers have shown that 30-40% of patients show aberrant loss of imprinting (LOI) of the IGF2 gene due to loss of DNA methylation in the maternal IGF2 allele, both in the tumor and in the tumor's neighboring normal mucosa cells (Cui et al, 1998(Cui et al, , 2003. About 10% of the normal human population show LOI of IGF2 in their peripheral blood cells and this population has a fivefold higher risk of developing colorectal cancer (Cui et al, 2003).…”
Section: Differentiation Plasticity In Normal and Cancer Stem Cells Jmentioning
confidence: 99%